Specific alterations of gut microbiota in patients with membranous nephropathy: A systematic review and meta-analysis - Zhang, Yumeng; Zhao, Jin; Qin, Yunlong; Wang, Yuwei; Yu, Zixian; Ning, Xiaoxuan; Sun, Shiren (Frontiers in Physiology, 2022)
Background: The pathogenesis of idiopathic membranous nephropathy (IMN) has not yet been thoroughly clarified, and gut dysbiosis may be a contributor to IMN. However, the characterization of gut microbiota in patients with IMN remains uncertain. Methods: Cochrane Library, PubMed, China National Knowledge Internet, Web of Science, and Embase were used to search for studies through 18 May 2022. A meta-analysis based on the standardized mean difference (SMD) with 95% confidence interval (CI) was conducted on the alpha diversity index. The between-group comparison of the relative abundance of gut microbiota taxa and the beta diversity were extracted and qualitatively analyzed. Results: Five studies were included involving 290 patients with IMN, 100 healthy controls (HCs), and 129 patients with diabetic kidney disease (DKD). The quantitative combination of alpha diversity indices indicated that although bacterial richness was impaired [ACE, SMD = 0.12, (−0.28, 0.52), p = 0.55, I2 = 0%; Chao1, SMD = −0.34, (−0.62, −0.06), p < 0.05, I2 = 36%], overall diversity was preserved [Shannon, SMD = −0.16, (−0.64, 0.31), p = 0.50, I2 = 53%; Simpson, SMD = 0.27, (−0.08, 0.61), p = 0.13, I2 = 0%]. The beta diversity was significantly varied compared to HCs or DKD patients. Compared to HCs, the abundance of Proteobacteria increased, while that of Firmicutes decreased at the phylum level. Furthermore, the abundance of Lachnospira were depleted, while those of Streptococcus were enriched at the genus level. Proteobacteria and Streptococcus were also increased compared to DKD patients. Conclusions: The expansion of Proteobacteria and depletion of Lachnospira may be critical features of the altered gut microbiota in patients with IMN. This condition may play an important role in the pathogenesis of IMN and could provide bacterial targets for diagnosis and therapy.